TRADISI RELIGI DAN SOSIOKULTURAL MASYARAKAT ACEH PADA RAMADHAN DAN IDUL FITRI DALAM MASA PANDEMI COVID-19 - Mirza Desfandi; Jakiatin Nisa; Ahmad Nubli Gadeng; Aida Muliana (Jurnal Masyarakat dan Budaya, 2021)
This article describes the phenomenon of the implementation of the Meugang and Kenduri Nuzululquran traditions in the months of Ramadan and Idulfitri 1441 H during the Covid-19 pandemic in Aceh. This paper is a literature review. The results of the study show that even though they are being hit by the Covid-19 pandemic, the people of Aceh during the month of Ramadan 1441 H still flocked to mosques to carry out worship. In addition, the tradition of Meugang and the feast of Nuzululquran is still being carried out. This is because the people of Aceh believe that by carrying out religious orders and carrying out the Meugang tradition and the tradition of sharing in the Nuzululquran feasts that have been carried out from generation to generation, will be able to keep them away from disasters and calamities. Conversely, if a lot of disobedience and disobeying His commands will bring disaster and disaster. Based on this, it is advisable for the public to carry out the tradition of Meugang and kenduri nuzulul quran or other traditions to always comply with the appeal of the government and also scholars by always carrying out health protocols in preventing the spread of Covid-19.